Modernization and Urban Water Governance Organizational Change and Sustainability in Europe - Bolognesi, Thomas (Palgrave Studies in Water Governance: Policy and Practice, 2018)
This book describes the impact of modernization on the organization and sustainability of Urban Water Systems in Europe (UWSEs). Bolognesi explains that the modernization of UWSEs was a regulatory shock that began in the 1990s and was put into action with the EU Water Framework Directive in the year 2000. This process sought to reorganize water governance in order to achieve certain sustainability goals, but it fell short of expectations. Modernization and Urban Water Governance provides an update on the organization and sustainability of UWSEs, while drawing from a comparative analysis of German, French, and English water models and an institutionalist explanation of the current situation. With a focus on transaction costs, property rights allocation and institutional environments, this book argues that the modernization of UWSEs tends to depoliticize these systems and make them more resilient but also limits their potential for sustainable management. This book will be relevant to those wishing to understand the real impacts of water reform in Europe according to national contingencies.